Pengaruh Kebiasaan Belajar Terhadap Prestasi Belajar Siswa Kelas VIII SMPN 1 Kaledupa - Dian Lestari; Darmita Darmita (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2021)
The formulation of the problem in this study is whether there is an effect of study habits on mathematics learning achievement of class VIII students of SMPN 1 Kaledupa. This type of research is ex-post facto. Ex-post facto research aims to find causes that allow changes in behavior, symptoms or phenomena caused by an event, or things that cause changes in the independent variable as a whole. Judging from the objective, this research is a causal research (correlation research). Correlation research is a study that involves the act of collecting data in order to determine whether there is a relationship and the level of the relationship between two or more variables. Based on the results of observation, evaluation and reflection in each cycle, it can be concluded that there is an effect of learning habits on the mathematics learning achievement of students of class VII SMP Negeri 1 Kaledupa, which can be proven by the F test, it is obtained that Fcount has a significant value of less than 0.05 or individually. as evidenced by the results of the t test, it is found that the t-count has a significant less than 0.05 and can be seen from the magnitude of the influence of the learning habits variable on mathematics learning achievement. Thus, the magnitude of the influence of study habits on mathematics learning achievement was 57.4%, the remaining 42.56% was influenced by other factors which were not examined in this study.